Long-term outcomes of drainless anatomical lung resection surgery for pulmonary malignancies - Ting-Fang Kuo; Mong-Wei Lin; Ke-Cheng Chen; Shuenn-Wen Kuo; Pei-Ming Huang; Jang-Ming Lee (Journal of Cardiothoracic Surgery)
Abstract Objective Drainless minimally invasive anatomical lung resection surgery for pulmonary malignancies is safe and feasible in terms of early postoperative outcomes. However, the quality of surgery in the long term remains uncertain. This study aimed to investigate the perioperative outcomes, 3-year overall, and disease-free survival rates of patients who underwent minimally invasive anatomical lung resection surgery with the drainless technique for pulmonary malignancies. Methods Fifty-eight patients who underwent drainless minimally invasive anatomical lung resection surgery for pulmonary malignancies (36 -lobectomy; 22 -segmentectomy) between November 2017 and June 2022 by a single surgeon were enrolled. Patients’ characteristics and perioperative, early postoperative, and long-term data were collected. The lymph node dissection stations and number, resection margin, 3-year overall and disease-free survival rates were assessed. Results The median age was 64 years. Forty-four patients were females (76%) and forty-seven patients were non-smokers (81%). The median five-factor modified frailty index was 1. Most patients had primary lung cancer; four (7%), 43 (74%), seven (12%), and three (5%) had stage 0, I, II, and III, respectively. The median lymph node dissection stations was four, and the number was 17. The resection margin was free in 98% of the cases. The 3-year overall survival rate was 98.3% in all patients, and 97.2% and 100% in the lobectomy and segmentectomy subgroups, respectively. The 3-year disease-free survival rate was 85.3% in all patients and 80.5% and 92.9% in the lobectomy and segmentectomy subgroups, respectively. Conclusion The drainless technique is safe and feasible for minimally invasive anatomical lung resection surgery for pulmonary malignancies in terms of early postoperative and long-term outcomes. However, further randomized controlled studies are warranted.